Evaluation of the Effectiveness of the Ameroro Dam in Mitigating Flood Risk within the Ameroro River Basin - Muh. Rivan Saranani; Evi Anggraheni (Acitya Wisesa: Journal of Multidisciplinary Research, 2026)
Recurrent flooding in the Ameroro Watershed, Konawe Regency, Southeast Sulawesi, Indonesia, has historically inundated between 1,500 and 2,000 hectares of downstream agricultural land and residential settlements, driven by peak discharges exceeding 400 m³/s that surpass the natural conveyance capacity of the Ameroro River. This study evaluates the flood risk reduction effectiveness of Ameroro Dam, a National Strategic Project with a total reservoir storage capacity of 101.92 million m³, through an integrated hydrological and hydraulic modeling framework. Hydrological modeling was performed using HEC-HMS, applying the SCS Curve Number method for rainfall loss estimation and the SCS Unit Hydrograph for runoff transformation across design return periods of 2, 5, 10, 25, 50, and 100 years. Hydraulic simulation was conducted using HEC-RAS two-dimensional unsteady flow analysis to produce spatially distributed inundation depth and flow velocity maps for pre-dam and post-dam conditions. Flood risk was subsequently quantified using the composite index framework prescribed by Indonesian National Disaster Management Authority Regulation No. 2 of 2012. Based on the dam’s as-built design specifications, the reservoir is projected to attenuate peak flood discharge by approximately 584 m³/s, representing a 66% reduction at the 100-year return period. Analysis of the risk framework further indicates that downstream sub-districts with high social vulnerability are likely to retain medium risk classifications under regulated discharge conditions, demonstrating that structural measures alone are insufficient. A combined structural and non-structural mitigation strategy is recommended to achieve acceptable residual risk levels across the downstream reach.